Convexity of the Krein space tracial numerical range and Morse theory - Nakazato, Hiroshi (2009)
In this paper we present a Krein space convexity theorem on the tracial-numerical range of a matrix. This theorem is the analogue of Westwick's theorem. The proof is an application of Morse theory.